Profile of Candida bloodstream infections among blood culture-positive patients at a tertiary care hospital - S. Shreya; K. Sandhya Bhat (Journal of Current Research in Scientific Medicine)
Background: Candidemia is a cause of concern today, due to their high rates of association with morbidity and mortality. Automated blood cultures are the gold standard tools for the evaluation of suspected cases of sepsis. This study was done to document the proportion of candidemia, Candida profile, susceptibility to fluconazole, and associated risk factors among suspected cases of sepsis. Materials and Methods: This descriptive study involved the retrospective analysis of data from 30 patients who were positive for Candida bloodstream infections. The patient demographic details and associated risk factors were documented. Candida isolates were identified by their colony morphology, germ tube test, growth character on CHROMagar Candida, and carbohydrate fermentation tests. Antifungal susceptibility testing to fluconazole was performed. Results: The overall prevalence of candidemia was 0.33%. The median age distribution of patients with culture-positive candidemia was 54.5 years. The associated risk factors among patients with candidemia were diabetes (60%), chronic kidney disease (26.7%), acute respiratory distress syndrome (23.3%), chronic liver disease (23.3%), and cerebrovascular accident (16.7%). The most common Candida species isolated was Candida tropicalis (46.7%), followed by Candida parapsilosis (13.3%), Candida krusei (10%), and Candida albicans (6.7%). The fluconazole sensitivity was documented to be 86% of isolates. Conclusion: Thorough knowledge of the background of candidemia, changing patterns of Candida profile, and resistance to first-line antifungals is essential to understand the presenting illness to its fullest potential and start appropriate empiric antifungal treatment while keeping in mind the risk factors.